Model of Actor Capability in The Implementation of Restorative Justice Policies to Achieve The Performance of The Ogan Ilir District Attorney's Organization. - Tandi, Marthen; Sobri, Kiagus Muhammad; Sriati, Sriati; Lionardo, Andries (Green Publisher Indonesia, 2025)
The restorative justice approach has been applied in Indonesia, especially in the settlement of juvenile criminal cases and complaints, based on Law Number 11 of 2012 and the Criminal Code. This study analyzes the Actor Capability Model in the Implementation of Restorative Justice Policy at the Ogan Ilir District Attorney's Office, referring to the Attorney General's Regulation No. 15 of 2020. The theory used includes the concept of restorative justice, the capability model, and the relationship between the prosecutor's ability to apply the concept. The research method is qualitative descriptive, with data obtained through interviews, surveys, observations, and documentation. Data analysis is carried out through collection, reduction, presentation, and the drawing of conclusions. The results show that the ability of the Ogan Ilir District Prosecutor's Office to implement restorative justice is quite good, covering technical, social, and conceptual aspects. However, there are challenges in the dimension of idealized policy, especially in the pattern of interaction between policymakers and target groups. The importance of the role of law enforcement officials—the police, prosecutors, and courts—in the implementation of this policy emphasizes the need for a dedicated organizational unit to focus on the tasks and objectives of restorative justice.